Manajemen Kepeserta Didikan dalam Pengembangan Kecerdasan Intelektual dan Emosional Peserta Didik - Waras Didik Susanto; Tatik Swandari (Lembaga Penelitian, Penerbitan dan Pengabdian (LP3M) IAI Al-Urwatul Wutsqo Jombang, 2021)
This article aims to describe and analyze: student recruitment and development in the development of intellectual-emotional intelligence of students at MTS. Ma'arif Randegansari Driyorejo Gresik. This article uses a qualitative approach with the type of case study research. The location of this research is MTS. Ma'arif Randegansari Driyorejo Gresik,. Data was collected using observation, structured and in-depth interviews and documentation. The analysis uses data reduction techniques, data presentation and conclusion drawing. Checking the validity of the findings is done by triangulation. Based on the process of data collection and analysis, researchers can conclude several things, namely: (1) Recruitment of new students at MTS. Ma'arif Randegansari Driyorejo Gresik,: active recruit approach with Walks-ins; new prospective students come to MTS. Ma'arif Randegansari Driyorejo Gresik, and registered, and Write-ins; prospective new students and their parents write a registration form. Implementation of Matsama: developing the cognition of new students in terms of divergent and convergent thinking skills. (2) Placement of students in MTS. Ma'arif Randegansari Driyorejo Gresik,: Abjad system; placement of learning in the classroom (intracurricular), The Dual Progress Plan Grouping; dividing students into several groups who have heterogeneous intelligence and are guided by a teacher (Self-Contained Classroom). Fingerprint system; placement of students in the development of talents and interests (extracurricular). (3) Student development in the development of intellectual-emotional intelligence: (a) intracurricular; learning in the classroom, (b) extracurricular; olympiad tutoring quark science, mathematics, English, tahfidz, scouts, guidance programs, discipline, reflection, and muhasabah.